Compliance to tobacco and alcohol zoning regulations around schools in Bangladesh, India, Pakistan and Sri Lanka using environmental mapping data - Lathika Athauda; Zoey Verdun; Petya Atanasova; Sajjad Ahmad; Ali Ahsan; Md Mokbul Hossain; Menka Loomba; Rajendra Pradeepa; Vindya Rajakaruna; Manuja Kaluarachchi; Anuradhani Kasturiratne; Khadija Irfan Khawaja; et al. (BMC Medicine)
Abstract Background The built environment around schools that are regularly accessed by young people is determined by governments, national and regional policies in each country or region. Zoning regulations for tobacco and alcohol sales are expected to restrict availability and access by young people. This study aimed to examine (non) compliance with tobacco and alcohol zoning regulations around schools in Bangladesh, India, Pakistan and Sri Lanka. Methods In a representative sample of geographic locations in Bangladesh, India North (Delhi) and India South (Chennai), Pakistan and Sri Lanka, the built environment was mapped by systematically walking all streets within the site boundary to collect data on different types of tobacco and alcohol retailers and schools. Data was collected on KoboToolBox, and the maps indicating zoning compliance were created using ArcGIS. Descriptive analysis of outlet compliance to the zoning laws was conducted at the national and school levels, with heterogeneity analyses done by school type, income level and outlet type for tobacco and alcohol. Results The zoning regulations for tobacco and alcohol differed among the settings ranging from 50 to 100 m for tobacco and absolute bans to 500 m for on-premise alcohol. Among the five different settings within the four countries, 441 areas were studied, including 3615 schools. Non-compliance with the zoning laws is evident in all jurisdictions for both tobacco and alcohol. Within restricted zones around schools (location non-compliant with zoning laws), 12–38% of outlets selling tobacco and 16% to 100% of outlets selling alcohol were identified. For supply non-compliance, 3–70% of shops within the school buffer zones were selling tobacco, while only 0.2–1% of shops were selling alcohol. Conclusions Non-compliance with tobacco and alcohol zoning regulations has been observed around schools in Bangladesh, India (North and South), Pakistan and Sri Lanka. Within each country, there was a higher percentage of alcohol outlets that were location non-compliant than for tobacco, except for South India. In India and Sri Lanka, there was a higher percentage of supply non-compliance for tobacco than alcohol. This study calls for governments to strictly enforce existing zoning regulations that are expected to restrict access to tobacco and alcohol for young people.